The Iliac Crest Osteomuscular Flap for Bony Reconstruction: Beast or Beauty? A Reassessment of the Value and Donor Site Morbidity in the CAD/CAM Era - Hilven, Paulien H.; Vranckx, Jan J. (Journal of Reconstructive Microsurgery, 2021)
Background The iliac crest bone flap (ICBF), based on the deep circumflex iliac artery, has a bad reputation regarding donor site morbidity. However, the ICBF has an ideal curvature and shape for occlusion-based hemimandibular reconstructions with rapid dental rehabilitation and for vertical class III maxillary reconstructions that require bony support and muscular bulk to fill cavities and to provide intraoral lining. Is this notorious donor site reputation still valid with modern flap procurement using computer aided design/computer aided manufacturing (CAD/CAM) and recipient-site closure techniques?Methods We performed a literature search of the public databases PubMed, Cochrane, Google Scholar, and Web of Science for papers using mesh keywords related to donor site morbidity of the ICBF. We report three illustrative case reports using our current protocols for oncologic bony resection and reconstruction, using in-house CAD/CAM and three-dimensional printing to procure a tight-fit ICBF and minimizing donor site morbidity.Results We found 191 articles in the PubMed database of which we considered 176 nonrelevant. Cochrane Library and Google Scholar database searches resulted in the inclusion of 11 additional papers. The second search resulted in 172 articles of which we used five after excluding nonrelevant papers. Accurate preoperative (CAD/CAM) planning, preservation of the anterior superior iliac spine (ASIS), and paying attention to thoroughly donor site closure make the ICBF a very valuable option for accurate maxillofacial reconstructions with very acceptable comorbidities. This corresponds with our clinical findings.Conclusion Dogma never is a good teacher; it remains elementary that routine “knowledge” is (re)questioned. Donor site morbidity of the ICBF is comparable to other bone flaps. The shape and bone stock of the ICBF is ideal and often may be first choice. In combination with CAD/CAM planning, the ICBF is an excellent option for specific maxillofacial reconstructions.
Keywords: vascularized iliac crest free flap; CAD/CAM planning; maxillofacial reconstruction